Leukemic infiltration of the ovary as an initial presentation of chronic myeloid leukemia in the chronic phase - Sekulić, Borivoj; Perčić, Ivanka; Dragičević Jojkić, Marina; Dokić, Marina; Panjković, Milana (Vojnosanitetski pregled, 2022)
Introduction. Extramedullary sites of leukemic proliferation, harboring an adverse outcome, are rare and usually found in the blastic phase of chronic myeloid leukemia. We report a case of a newly diagnosed patient with chronic myeloid leukemia in the chronic phase, with leukemic infiltration of the right ovary on disease presentation. Case report. The patient presented with abdominal pain, leukocytosis, and anemia. A peripheral blood smear indicated chronic myeloid leukemia, and cytoreductive treatment was started. Due to the worsening of the abdominal pain, computed tomography was done. It revealed a cystic tumor of the right ovary. The tumor was surgically removed. Bone marrow examination confirmed the diagnosis of chronic myeloid leukemia in the chronic phase. Immunohistochemical analysis of the ovarian tumor showed leukemic infiltration with 5% of blasts. The patient was treated with imatinib for one year. Due to treatment failure, imatinib was switched to nilotinib. Allogeneic stem cell transplantation was considered. Conclusion. This case highlights the critical role of the multidisciplinary team approach and close treatment monitoring to achieve the best possible outcome in these patients.